Multi-spécificité, mobilités pastorales et environnement en Mongolie - Jeanne Riaudel (EchoGéo)
Mongolian pastoralism is a way of life that involves the frequent movement of both people and animals on a daily and annual basis. This mobility is influenced by a variety of factors, including economic, social, cultural, and environmental conditions. This article is the result of a 3-month fieldwork in the Shinejinst district of Bayanhongor province. It seeks to present the method and some results of a survey on the dynamics and issues of a nomadic pastoral economic model based on the mobility of multi-species herds, by questioning the capacity of human and animal adaptation to new environmental constraints.